A metamaterial scaffold beyond modulus limits: enhanced osteogenesis and angiogenesis of critical bone defects - Yu Qin; Zehao Jing; Da Zou; Youhao Wang; Hongtao Yang; Kai Chen; Weishi Li; Peng Wen; Yufeng Zheng (Nature Communications)
Abstract Metallic scaffolds have shown promise in regenerating critical bone defects. However, limitations persist in achieving a modulus below 100 MPa due to insufficient strength. Consequently, the osteogenic impact of lower modulus and greater bone tissue strain ( > 1%) remains unclear. Here, we introduce a metamaterial scaffold that decouples strength and modulus through two-stage deformation. The scaffold facilitates an effective modulus of only 13 MPa, ensuring adaptability during bone regeneration. Followed by a stiff stage, it provides the necessary strength for load-bearing requirements. In vivo, the scaffold induces > 2% callus strain, upregulating calcium channels and HIF-1α to enhance osteogenesis and angiogenesis. 4-week histomorphology reveals a 44% and 498% increase in new bone fraction versus classic scaffolds with 500 MPa and 13 MPa modulus, respectively. This design transcends traditional modulus-matching paradigms, prioritizing bone tissue strain requirements. Its tunable mechanical properties also present promising implications for advancing osteogenesis mechanisms and addressing clinical challenges.